PERBEDAAN HASIL BELAJAR KOMPETENSI MENJELASKAN PROSES-PROSES MESIN KONVERSI ENERGI MENGGUNAKAN MODEL PEMBELAJARAN SNOWBALL THROWING DENGAN MODEL PEMBELAJARAN LANGSUNG - Irawan, Zudi (Journal of Mechanical Engineering Learning, 2014)
This study aims at finding out if the differences and a significant increase in learning outcomes between the experimental group were taught by Snowball Throwing learning model and the control group were taught with direct instruction on competencies Explaining Processes Energy Conversion Machine. In this study research design pre-experimental design with a static group comparison approach. The population was class X Light Vehicle Engineering (X TKR) SMK N 10 Semarang academic year 2013/2014. Samples was determined using cluster random sampling technique and derived class X TKR 2 as the experimental group and class X TKR 3 as a control group. The results of the analysis of data showed the average value of the initial data for the experimental group was 51.68 then after the experiment increased to 65.33 which means an increase of 13.65 (26%) and for the control group the average value of the initial data for 53.94 then after the experiment increased to 63.97 which means an increase of 10.03 (19%). It concluded there was no difference and a significant improvement in learning outcomes, however the use of Snowball Throwing learning model has been better than direct instruction because of increased learning outcomes experimental group is greater than the control group.